2020
DOI: 10.1029/2019jc015773
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the Distribution and Fate of Sedimentary Polycyclic Aromatic Hydrocarbons Within the Estuarine‐Inner Shelf Areas of the East China Sea: Response to Human‐Induced Catchment Change

Abstract: Human-induced changes in river catchments, such as damming, can affect estuarine depositional settings and further affect the transport of sediments and associated pollutants. Polycyclic aromatic hydrocarbons (PAHs) in surface sediments from the East China Sea (ECS) at two time nodes (2006 and 2018) were compared to understand the response of PAHs to human-induced catchment changes. PAH concentrations in the ECS ranged from 8-414 ng g −1 (dry weight), with a mean value of 112 ± 77 ng g −1 , relatively low th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
(105 reference statements)
1
3
0
Order By: Relevance
“…While the variations in the sedimentary OC can be partly attributed to the reduction in the terrestrial POC input, the hydrodynamic process is also considered a factor affecting the fate of sedimentary OC in marginal seas (Bao et al, 2018, 2019; Bianchi et al, 2018; Bröder et al, 2016, 2018). We have confirmed that the sedimentary environment in the study area changed due to the sharp reduction in the sediment load (Wang, Hao, Feng, Zhang, Li, et al, 2020), which would inevitably affect the dispersal and burial of POC. The sediment flux discharged from the Changjiang River to the ECS dropped from 340 Mt yr −1 in 1986–2002 to 145 Mt yr −1 after the TGR impoundment, which is insufficient to maintain the geomorphic stability of the CSDMD (Yang et al, 2018).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…While the variations in the sedimentary OC can be partly attributed to the reduction in the terrestrial POC input, the hydrodynamic process is also considered a factor affecting the fate of sedimentary OC in marginal seas (Bao et al, 2018, 2019; Bianchi et al, 2018; Bröder et al, 2016, 2018). We have confirmed that the sedimentary environment in the study area changed due to the sharp reduction in the sediment load (Wang, Hao, Feng, Zhang, Li, et al, 2020), which would inevitably affect the dispersal and burial of POC. The sediment flux discharged from the Changjiang River to the ECS dropped from 340 Mt yr −1 in 1986–2002 to 145 Mt yr −1 after the TGR impoundment, which is insufficient to maintain the geomorphic stability of the CSDMD (Yang et al, 2018).…”
Section: Resultssupporting
confidence: 70%
“…Therefore, the seabed sediment in the CSDMD was eroded and transported southward by coastal currents. Long periods of insufficient sediment supply have caused erosion to spread further into the ZMCMB (Gao et al, 2019; Wang, Hao, Feng, Zhang, Li, et al, 2020). Large amounts of fine‐grained particles in the seabed sediment have been washed away, which has significantly changed the sediment grain sizes and components in the study area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the marine environment, the water transport ability of CPs mainly depends on their discharge, deposition, transfer, mobility, and persistence. ,,, A large amount of CPs in the water body was input into coastal waters, resulting in higher levels of CPs than in offshore waters. , For example, high concentrations of SCCPs and MCCPs were detected in the Pearl River Delta, China, with river runoff as the primary source . After being discharged into the ocean, high concentrations of CPs in the coastal ocean can be subject to long-range transport and were then potentially brought into the offshore waters via the carrier of the ocean and tidal currents. ,,, On the other hand, CPs are readily adsorbed by sediments due to low water solubility and high organic carbon partition coefficient. , The transport ability of CPs by ocean currents varies in different CP congeners due to the diversity of persistence, volatility, and solubility.…”
Section: Sources and Transport Of Cps In The Marine Environmentmentioning
confidence: 99%